Investigation of Art Therapy Applications in Geriatric Rehabilitation from the Perspective of Occupational Therapy - Alioğlu D.; Sarışahin S.; Zengin G.; Uğurlu Ü. (My University, 2025)
AbstractAim:This review aims to systematically examine art therapy practices applied within the scope ofoccupational therapy for geriatric individuals.Method:A literature search was conducted using the keywords \"art therapy\" OR \"music therapy\" OR \"dancetherapy\", \"older adults\" OR \"geriatric individuals\", and \"occupational therapy\" OR \"ergotherapy\". TheBoolean search method was employed in the PubMed and OTseeker databases.Results:Seven articles published between 2017 and 2024 that met the inclusion criteria were identified.Among them, four were research articles (57%), two were randomized controlled trials (29%), and one wasa descriptive study (14%). The characteristics and findings of these studies were organized under threethematic categories: dance therapy practices in geriatric rehabilitation, art and craft practices in geriatricrehabilitation, and other practices in geriatric rehabilitation.Conclusion:The reviewed interventions were found to be effective in enhancing cognitive functioning,reducing symptoms of depression, and improving overall quality of life in geriatric populations.Furthermore, the importance of engaging older individuals in personalized, meaningful, and purposefuloccupations was emphasized as a means to alleviate behavioral symptoms, reduce caregiver burden, andminimize caregiving time.Keywords:Occupational therapy, art therapy, geriatric individuals.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (Med); Clinical Medicine (Med)